Pola Artikulasi Aspirasi Nahdlatul Ulama sebagai Kelompok Kepentingan (Studi Kasus: Tinjauan Pembahasan dan Rekomendasi Hukuman Mati Koruptor dan Boykot Pajak dalam Musyawarah Nasional Alim Ulama dan Konferensi Besar Nahdlatul Ulama 2012) - Miqdad Haqqony; Yuwanto .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
Interest group is a continuation of political participation in a political system.Interest group can be considered as an entity that seeks to articulate aspiration of its follower to the government of the state, without attempts to gain certain positions of public officials. One of prominent interest groups in Indonesia is Nahdlatul „Ulama. The existence of Nahdlatul „Ulama should be recognized as an interest group that is adequate and competent to transform condition of the nation-state into expectation of the society . Because of its comprehensive organizational structure and supported by a large number of followers, Nahdlatul „Ulama is considered able to act as opinion leader for people, particularlly for its followers, in order to respond situation that is occured in Indonesia.In the contemporary era, the existence of the Nahdlatul „Ulama can be assessed from results of National Conference of The „Ulama and Great Conference of Nahdlatul Ulama 2012. Two of four recommendations issued from the conference are corruption and tax fraud which are important to be eradicated for the sake of the wider community.In articulating, Nahdlatul „Ulama tended to combine the “top-down”, as form of guiding for the followers and “bottom-up”, as form of awareness of the problems. Related to issues of corruption and tax fraud, Nahdlatul „Ulama integrated the „Ulama‟s opinion and the expert‟s. It also based on the condition or situation that occurs in Indonesia. Eventually, the recommendations and the actions taken by Nahdlatul „Ulama aims to persuade the government to act seriously in solving corruption and tax fraud, as form of public interest articulation and moral support.